Genome-wide identification of non-coding RNAs interacted with microRNAs in soybean - Ye, Chu-Yu; Xu, Hao; Shen, Enhui; Liu, Yang; Wang, Yu; Shen, Yifei; Qiu, Jie; Zhu, Qian-Hao; Fan, Longjiang (Frontiers in Plant Science, 2014)
A wide range of RNA species interacting with microRNAs (miRNAs) form a complex gene regulation network and play vital roles in diverse biological processes. In this study, we performed a genome-wide identification of endogenous target mimics (eTMs) for miRNAs and phased-siRNA-producing loci (PHAS) in soybean with a focus on those involved in lipid metabolism. The results showed that a large number of eTMs and PHAS genes could be found in soybean. Additionally, we found that lipid metabolism related genes were potentially regulated by 28 miRNAs, and nine of them were potentially further regulated by a number of eTMs with expression evidence. Thirty-three miRNAs were found to trigger production of phasiRNAs from 49 PHAS genes, which were able to target lipid metabolism related genes. Degradome data supported miRNA- and/or phasiRNA-mediated cleavage of genes involved in lipid metabolism. Most eTMs for miRNAs involved in lipid metabolism and phasiRNAs targeting lipid metabolism related genes showed a tissue-specific expression pattern. Our bioinformatical evidences suggested that lipid metabolism in soybean is potentially regulated by a complex non-coding network, including miRNAs, eTMs and phasiRNAs, and the results extended our knowledge on functions of non-coding RNAs.